Turkey's Military Intervention against PYD (Partiya Yekiti A Demokratik) in the Syrian Region - Shinta Damayanti; Muhammad Syauqillah (Budapest International Research and Critics University, 2022)
This paper aims to analyze how Turkey's military intervention against the PYD group in Syria. As the effect of the Arab Spring, Syria has been encountering a civil war that involves not only state actors but also non-state actors such as the YPG/PYD group or the Democratic Union Party to gain recognition and political sovereignty for Kurdish groups in Syria. The YPG/PYD is an affiliate of the PKK (Kurdistan Workers' Party) in Turkey, which is considered a terrorist group by the government because of its actions opposed government policies since the independence of modern Turkey era. In the midst of political instability in Syria, the Turkish government believes that the political nature and military power of the PKK and its allies in the region can jeopardize Turkey’s security and politic stability, which geographically borders Syria. This research uses descriptive qualitative method through literature review method. Through J.G. Starke and Anthony F. Lang's theory of intervention and Barry Buzan’s National Interest, the author found that Turkey's intervention was due to the losses it would incur if the PYG/PYD's ability to strengthen Kurdish groups in Syria.